The marmoset monkey: a multi-purpose preclinical and translational model of human biology and disease - ’t Hart, Bert A.; Abbott, David H.; Nakamura, Katsuki; Fuchs, Eberhard (Drug discovery today, 2012)
► The marmoset offers valid preclinical models in a wide range of clinical disorders. ► Due to the small body weight low amounts of test compound are needed. ► For placebo-controlled evaluation of a new therapy bone marrow chimeric twins that are immunologically highly similar can be used. ► The anatomical similarity of the marmoset and human brain provides a useful experimental model for brain imaging studies. The development of biologic molecules (monoclonal antibodies, cytokines, soluble receptors) as specific therapeutics for human disease creates a need for animal models in which safety and efficacy can be tested. Models in lower animal species are precluded when the reagents fail to recognize their targets, which is often the case in rats and mice. In this Feature article we will highlight the common marmoset, a small-bodied nonhuman primate (NHP), as a useful model in biomedical and preclinical translational research.